2020
DOI: 10.5902/2179460x33089
|View full text |Cite
|
Sign up to set email alerts
|

Uso de Geotecnologias no Estudo da Degradação das Terras da Bacia do Rio Sucuru, na Paraíba

Abstract: The objective was to map spatially and temporally the degradation of the lands of the Sucuru River basin in the region of Cariri Paraibano. The SPRING 5.2.7 program was used for the digital processing of orbital images and the photointerpretative keys for evaluation of levels of degradation, field visits, consultations with literature and public agencies. There was a regeneration of the areas that previously were in the levels of degradation very serious and moderate severe, due to factors such as the drought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…This class includes areas with crops and soils prepared for cultivation or fallow (ALENCAR, 2008). Cultivation areas are affected by the irregular rainfall in the region (SANTOS, 2015). Our data are comparable to those shown by Alencar (2008) and Santos (2015) with results of 36.51 and 45.59% of Sparse Vegetation and Exposed Soil, confirming the importance of this activity in the region.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…This class includes areas with crops and soils prepared for cultivation or fallow (ALENCAR, 2008). Cultivation areas are affected by the irregular rainfall in the region (SANTOS, 2015). Our data are comparable to those shown by Alencar (2008) and Santos (2015) with results of 36.51 and 45.59% of Sparse Vegetation and Exposed Soil, confirming the importance of this activity in the region.…”
Section: Resultssupporting
confidence: 90%
“…Previous studies carried out in the Sucuru River Basin reported lower values of Dense Vegetation. For example, Santos (2015) reports that 2.32% of the area was covered by dense vegetation in 1990, while in 2013, this vegetation Revista Verde 17:4 (2022) 235-241 occupied 10.57%. Abandoned pastures in ecological regeneration processes may be increasing the dense vegetation areas over time (SANTOS 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations